Schaum's outline of theory and problems of trigonometry with calculator-based solutions - Ayres, Frank 1901- (Schaum's outline series, 1999)
Focusing on plane trigonometry, this book summarizes the geometry properties and theorems that prove helpful for solving trigonometry problems. It also explains the algebraic processes and the basic trigonometric relations.